PENGARUH PEMAHAMAN FATWA MUI TERHADAP MINAT BELI MASYARAKAT MUSLIM PADA PRODUK ISRAEL DAN YANG TERAFILIASI - Ardi, Unggul Suryo; Raharjo, Raharjo; Nursodik, Nursodik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
The conflict between Palestine and Israel has caused mixed responses in society. This war which claimed tens of thousands of lives gave rise to various humanitarian actions, one of which was the response of the Indonesian Ulama Council (MUI) which issued a fatwa regarding the legal status of support for the Palestinian struggle, namely a fatwa discussed the clause regarding the prohibition on consuming Israeli and affiliated products. This research aims to identify how much influence the understanding of MUI Fatwa No. 83 of 2023, regarding the Muslim community's buying interest in Israeli and affiliated products. This quantitative research uses a data collection technique in the form of a questionnaire distributed via Google Forms to the Muslim community in Semarang, and the data analysis technique used is simple regression using the W-Stats version 2.0 program to process the data. This research uses 1 independent variable, namely Understanding MUI Fatwa No. 83 in 2023, and 1 dependent variable, namely buying interest. Data was obtained from questionnaires distributed to 50 subjects from the Semarang Muslim community who were selected using a probability sampling technique using a simple random sampling method and measured using a Likert scale. The research results show the influence of understanding MUI Fatwa No. 83 Yr. 2023 is a significant year for the lack of public interest in purchasing Israeli and affiliated products. Where the regression coefficient value is 2.011% (0.02) which is smaller than 5% (0.05). The public's understanding of fatwas that influence purchasing interest in Israeli products and affiliated ones is a behavior or attitude in line with Ibn al-Qayyim's concept of saddu al-dzari'ah. In this context, avoiding the purchase or consumption of such products serves as a means of preventing potential harm (mafsadat) and danger (mudharat).